Mantras, Nature, and Spirituality: Ecocriticism in Traditional Healing Mantras in Karimunting Village - Hubbi Saufan Hilmi; Achmad Sultoni; Titi Setiyoningsih; Hariyadi Hariyadi (Journal of Language and Literature, 2025)
The inclusion of the natural environment and spiritual values in traditional healing mantras has been part of the lives of traditional communities in various cultures around the world, including the Malay community in Karimunting village, West Kalimantan, Indonesia. This study aims to describe the elements of the natural environment and spiritual values in the healing mantras of the Malay community in Karimunting Village by applying Greg Garrard’s ecocriticism approach. The data in this study was collected through observation and in-depth interviews with three belian in Karimunting village. The data obtained was subsequently recorded, transcribed, and analyzed using thematic analysis techniques. The research findings reveal that there are ten healing mantras practiced by the belian of the Malay community in Karimunting Village. Each mantra functions not only as a medium of healing but also as a representation of the interconnectedness between humans, the natural environment, and spiritual forces. Elements of the natural environment are reflected in the use of components such as leaves, water, wood, stones, wind, and animals, which are positioned as active entities possessing healing energy and symbols of ecological balance. Meanwhile, the dimension of spirituality is manifested through religious diction, such as the invocation of the names of Allah and the Prophet Muhammad, underscoring the belief that recovery ultimately originates from Divine power. This research contributes not only as an inventory of oral literature and local wisdom of the Malay community in utilizing their natural environment but also as a reference for similar research in the future.